2015
DOI: 10.1007/s40520-015-0368-6
|View full text |Cite
|
Sign up to set email alerts
|

Episodic future thinking: the role of working memory and inhibition on age-related differences

Abstract: The ability to remember past events and imagine future events (episodic future thinking-EFT) has been shown to decline with aging. However, only few studies have analyzed the cognitive mechanisms involved in EFT in both young and older adults. The present study examined the role of working memory and inhibition on age-related differences between young and older adults in EFT, in response to short sentences reflecting common events, some of which were repeated in both conditions (past and future). Thirty-seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
(68 reference statements)
3
18
0
1
Order By: Relevance
“…However, the lack of association in the picture description task speaks against this possibility: if people are distracted by task-irrelevant information, then a negative trend was expected between internal (task-relevant) and external (task-irrelevant) details irrespective of the episodic/non-episodic nature of the task. Relevant to this point, Zavagnin, De Beni, Borella, and Carretti (2016) found that for future imaginations, reduced inhibition ability was associated with a greater production of external details with age, but not with a lowered production of internal details, further suggesting that inhibition alone does not account for the pattern of increased external and decreased internal details at the event level. Moreover, Zavagnin et al (2016) found no association between inhibition and external details for remembered events, potentially implicating different mechanisms in the production of irrelevant content for memory retrieval and novel event simulation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the lack of association in the picture description task speaks against this possibility: if people are distracted by task-irrelevant information, then a negative trend was expected between internal (task-relevant) and external (task-irrelevant) details irrespective of the episodic/non-episodic nature of the task. Relevant to this point, Zavagnin, De Beni, Borella, and Carretti (2016) found that for future imaginations, reduced inhibition ability was associated with a greater production of external details with age, but not with a lowered production of internal details, further suggesting that inhibition alone does not account for the pattern of increased external and decreased internal details at the event level. Moreover, Zavagnin et al (2016) found no association between inhibition and external details for remembered events, potentially implicating different mechanisms in the production of irrelevant content for memory retrieval and novel event simulation.…”
Section: Discussionmentioning
confidence: 91%
“…However, it has previously been shown that in most experiments the episodic specificity induction increases internal details, but does not decrease external details (Madore et al, 2014; Madore, Jing, et al, 2016; Madore & Schacter, 2014, 2016; Madore, Szpunar, Addis, & Schacter, 2016; but see Jing, Madore, & Schacter, 2016; Madore, Addis, & Schacter, 2015). Furthermore, different types of future imaginations can alter the amount of internal details generated, with no concurrent effects on external details (de Vito, Neroni, Gamboz, Della Sala, & Brandimonte, 2015; see also Neroni, Gamboz, De Vito, & Brandimonte, 2016), and age-related decreases in internal details have been reported even when the number of external details does not differ with age (Madore & Schacter, 2014; Zavagnin et al, 2016). Future research would benefit from considering the nature of the dependence of the episodic and semantic processes involved in autobiographical event retrieval and simulation.…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation for our findings is that high-level construal, such as thinking about the distant future, may engage executive processes involved in working memory maintenance and inhibition of prepotent long-term memory representations more than low-level construal. Indeed, several studies indicate that imagining a future event draws heavily on working memory and other executive processes required for analytical problem solving (e.g., D’Argembeau et al, 2010 ; Zavagnin et al, 2016 ). It is expected that far-future priming would draw more heavily upon these processes than near-future priming because an event in the near future is very similar to an event in the present.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was designed to investigate whether affective factors account for this age-related pattern of future thinking by addressing, first, the lack of specificity, and second, the subjective experience of future thinking. Several cognitive factors have been identified as contributing to the age-related weakening in future thinking, including executive functions, working memory and visuospatial processing (Cole, Morrison, & Conway, 2013;Zavagnin, De Beni, Borella, & Carretti, 2015).…”
Section: Introductionmentioning
confidence: 99%